Verslunarhús Nathan & Olsen við Austurstræti. Hornsteinn Guðjóns Samúelssonar að nýjum miðbæ Reykjavíkur - Seelow, Atli Magnus (2012)
After the great fire in downtown Reykjavík in 1915, Guðjón Samúelsson designed the office building for Nathan & Olsen in Austurstræti 16 (1916-1917) as a first major step towards reconstructing the city centre.It is both on an urban as well as a stylistic level a cornerstone for the future of Reykjavík:On the one hand, it represents a new type of commercial building, on the other hand it is exemplary for the different influences in Guðjón Samúelsson's early work.